Compressive Optic Neuropathy Secondary to a Lateral Rectus Muscle Dermoid Cyst. Issue 3 (May 2015) - Tannan, Anjali; Jhaveri, Miral; Moftakhar, Roham; Munich, Stephan; Harbhajanka, Aparna; Cohen, Adam J.
<x xml:space="preserve">Abstract</x> A 48-year-old man presented 2 weeks after sudden OS vision loss. On examination, the patient had decreased OS visual acuity, an ipsilateral afferent pupil defect, and proptosis. MRI of the orbit with and without gadolinium showed a large, enhancing heterogeneous mass extending to the orbital apex. Uncomplicated resection was performed and pathology was consistent with a dermoid cyst. Postoperatively, the patient had improved visual acuity and minimal lateral rectus dysfunction. There are only 4 reported cases of dermoid cysts located within the lateral rectus muscle, albeit this is the first case describing a compressive optic neuropathy in the setting of an orbital dermoid cyst.